striga exposed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Striga: small seeds, big lossesStriga, a parasitic weed of most savannah crops, is gaining ground in Africa and farmers have only limited weapons against it. Its control should therefore be added to the list of priorities for research Over the last...